Milk intake reduced the prevalence of hypertension by decreasing total arsenic levels in fasting serum in Japanese residents - Tingchao He; Yuqi Deng; Nobutaka Ohgami; Takumi Kagawa; Akira Tazaki; Akihito Harusato; Shoko Ohnuma; Hisao Naito; Takashi Tamura; Kenji Wakai; Masashi Kato (Ecotoxicology and Environmental Safety, 2025)
Background: Exposure to arsenic increases the risk of hypertension. Indeed, a high level of arsenic in human serum, a reliable biomarker of arsenic exposure, was shown to be linked to increased prevalence of hypertension among a study of Japanese residents. However, no beneficial food that decreases the risk of arsenic-mediated hypertension has been determined by considering intake scores of multiple foods. Methods: The comprehensive effects of combined beverage intake on the risk of hypertension, mediated by decreased levels of total arsenic in fasting serum, were investigated among the same group of 2706 residents. Results: Our generalized linear regression analysis for each beverage showed significant negative associations of serum arsenic levels with milk and vegetable juice intake scores among 11 beverages. Weighted quantile sum (WQS) and Bayesian kernel machine regression (BKMR) analyses of combined beverage intake scores reveal that milk was the beverage most strongly associated with lower serum arsenic levels. Subsequent causal mediation analysis further showed that increased milk intake reduced the prevalence of arsenic-mediated hypertension by lowering serum arsenic levels. Additionally, our cell-free assay revealed the adsorption-modifying effect of milk on arsenic components in a popular fish meat. An in vivo assay confirmed that milk intake significantly decreased total serum arsenic levels in mice. Conclusions: Our multidisciplinary approach, combining epidemiological, chemical and animal studies, suggests that milk consumption has a beneficial effect in reducing the prevalence of arsenic-induced hypertension by decreasing arsenic absorption. Considering the global trend for increased consumption of fish meat with high levels of total arsenic, milk may be globally useful for reducing the risk of arsenic-mediated hypertension.